The Role of Cingulate Cortex in Vicarious Pain. (26th February 2015) - Yesudas, Esther H.; Lee, Tatia M. C.
Abstract : Vicarious pain is defined as the observation of individuals in pain. There is growing neuroimaging evidence suggesting that the cingulate cortex plays a significant role in self-experienced pain processing. Yet, very few studies have directly tested the distinct functions of the cingulate cortex for vicarious pain. In this review, one EEG and eighteen neuroimaging studies reporting cingulate cortex activity during pain observation were discussed. The data indicate that there is overlapping neural activity in the cingulate cortex during self- and vicarious pain. Such activity may contribute to shared neural pain representations that permit inference of the affective state of individuals in pain, facilitating empathy. However, the exact location of neuronal populations in which activity overlaps or differs for self- and observed pain processing requires further confirmation. This review also discusses evidence suggesting differential functions of the cingulate cortex in cognitive, affective, and motor processing during empathy induction. While affective processing in the cingulate cortex during pain observation has been explored relatively more often, its attention and motor roles remain underresearched. Shedding light on the neural correlates of vicarious pain and corresponding empathy in healthy populations can provide neurobiological markers and intervention targets for empathic deficits found in various clinical disorders.